2009
DOI: 10.1159/000207519
|View full text |Cite
|
Sign up to set email alerts
|

Cytological studies of recombination in rhesus males

Abstract: An immunofluorescence approach was used to directly examine meiotic recombination events in 483 pachytene spermatocytes from 11 male rhesus monkeys. Specifically, we examined the nuclear localization patterns of the DNA mismatch repair protein MLH1, known from analyses of other mammalian species to be a useful marker of meiotic cross-overs. Our results indicated that rhesus pachytene spermatocytes contain approximately 40 cross-overs per cell, corresponding to about one cross-over per chromosome. The chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 37 publications
8
23
0
Order By: Relevance
“…Both species have average MLH1 foci counts that approximate their autosomal chromosome numbers (Table 1), indicating that very rigid regulatory mechanisms must be in place to ensure that one (and usually only one) crossover is allocated to a given chromosome. In addition, both of these species have fewer MLH1 foci than chromosome arms (Table 1), complementing previous assertions that only one crossover per chromosome is necessary for correct homolog segregation Hassold et al 2009), at least in some taxa.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Both species have average MLH1 foci counts that approximate their autosomal chromosome numbers (Table 1), indicating that very rigid regulatory mechanisms must be in place to ensure that one (and usually only one) crossover is allocated to a given chromosome. In addition, both of these species have fewer MLH1 foci than chromosome arms (Table 1), complementing previous assertions that only one crossover per chromosome is necessary for correct homolog segregation Hassold et al 2009), at least in some taxa.…”
Section: Resultssupporting
confidence: 84%
“…A minimum of one crossover per chromosome arm is required to ensure the correct alignment of homologous chromosomes at the metaphase plate and their proper segregation during meiosis I, although recent studies have suggested that this constraint could be relaxed to one crossover per chromosome Hassold et al 2009). The average number of recombination events per autosome or per autosomal arm still varies markedly among the eight rodent taxa examined here (Table 1), suggesting that observed variation in raw MLH1 foci counts does not solely derive from differences in gross genome organization among rodent species.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, longer chromosomes displayed more MLH1 foci and a significant correlation between the autosomal SC length and number of MLH1 foci was found. A similar covariance was observed in humans [Lynn et al, 2002] and rhesus monkeys [Hassold et al, 2009]. The distribution of recombination events along individual bivalents was influenced by interference, as reported previously for other mammalian species [Froenicke et al, 2002;Sun et al, 2004;Basheva et al, 2008;Borodin et al, 2008;Yang et al, 2011].…”
Section: Discussionsupporting
confidence: 84%
“…This difference might be caused by interindividual variability or by different scoring criteria, because signals at the ends of SCs and at SC overlaps were not counted by Hart et al The frequency of spermatocytes with one or more autosomal bivalents lacking recombination (8.3-15.7%) was within the range reported for other mammals (5% in humans, Sun et al [2006b]; 16.8% in rhesus monkeys, Hassold et al [2009]). …”
Section: Discussionmentioning
confidence: 95%
“…In meiosis, heterodimers of MLH1 with another MutL DNA repair homologue, MLH3, are essential for wild-type levels of crossing over in budding yeast, mammals and plants [Baker et al, 1996;Hunter and Borts, 1997;Lipkin et al, 2002;Jackson et al, 2006] The discovery that MLH1 and MLH3 form foci on chromosomes during meiotic prophase, and that these foci numbers and distribution correlate with the known frequency and distribution of COs in mice and humans [Baker et al, 1996;Lipkin et al, 2002] allowed cytological mapping of CO events along individual chromosomes [Froenicke et al, 2002]. Analysis of MLH1 foci along the meiotic chromosome axes provided information on genetic recombination rates and the nature of genetic interference in mammals [Anderson et al, 1999;Lynn et al, 2002;Hassold et al, 2004;de Boer et al, 2006;Cheng et al, 2009;Hassold et al, 2009].…”
mentioning
confidence: 99%